UNILATERAL CHANGE OR REPLACEMENT OF THE PPJB DEED NUMBER BY NOTARY WITHOUT THE CONSENT OF THE PARTIES (CASE STUDY OF DECISION NUMBER 35/PID/B/2022/PN.TPG) - Yulius Chandra (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
One of the special powers of a notary is to make a deed in the land sector in the form of making a PPJB deed for parties who have agreed to carry out a land sale and purchase transaction. For some reason, the notary has made changes to the deed number unilaterally without the knowledge of the parties so that his actions have violated the applicable legal procedures. This article raises issues regarding the validity of changing the deed number and the legal implications of the PPJB deed and the notary's responsibility for this action. Based on the results of the study, the notary's actions were a form of error and violated UUJN provisions, which had the implication that the deed had no legal force because it was degraded into an underhand deed and the aggrieved party could claim compensation from the notary. Considering that there is a criminal element, the form of accountability of a notary can be criminally prosecuted and can be temporarily dismissed from 3 to 6 months by the Supervisory Board or the termination can adjust to the length of the criminal court decision.